CHINA THROUGH THE PRISM OF GLOBAL TRANSFORMATION (PHENOMENON OF GLOBALIZATION) - Остап'як, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Development study of one of the biggest and most powerful East Asian countries has been conducted. The author attempts to analyze further development of the mentioned country on a global basis. The positions and systems of influence in the Asia and Pacific Ocean region and strengthening of Chinese influence in Asian political system have been studied. The leading role of China after dissolution of the bipolar world and its competition with the USA and Russian Federation has been mentioned about. A complex of social, political, and economical reforms in the PRC that led to strengthening of the political influence in the international relations system has been analyzed. A possibility of effective study and utilization of Chinese experience in Ukrainian politics has been emphasized.